Penyediaan Ruang Terbuka Publik Sebagai Upaya Pemenuhan Hak Warga Negara dan Menunjang Berjalannya Demokrasi - Fadhilla Nur Laila; Fatma Ulfatun Najicha (Lembaga Penelitian dan Pengabdian Universitas Negeri Manado, 2023)
Citizens as social people need to provide space to express aspirations or interactions with others. Public open space is a space that provides freedom for citizens to be able to access and use it. However, in providing it, especially in urban areas, there are limitations to the availability of land. Urban activities that continue to grow are not proportional to the availability of urban land. This sometimes makes it difficult for people to access public open spaces. Therefore, this research wants to examine the provision of public open space as an effort to fulfill citizens' rights and support the functioning of the country's democracy. Through a qualitative descriptive approach, it is known that the availability of public space is very useful for social interaction in society. Public space can be part of a democratic country because it gives freedom to its citizens. In addition, the provision of this public space is also a form of embodiment of the values of Pancasila